KERAGAMAN PENERAPAN PENDIDIKAN GIZI DI SEKOLAH DASAR (SD) DAN MADRASAH IBTIDAIYAH (IM) DALAM PELAKSANAAN PMT-AS DI PEDESAAN DI LAMPUNG TENGAH - Hermina Hermina; Tjetjep S. Hidayat; Trintrin T. Mudjianto; Djoko Susanto (Persagi, 1998)
The program of supplementary feeding for Elementary School children has been implemented for several years. One of the multiple purposes of the program is to improve understanding and knowledge of nutrition for children and teachers through nutrition education and feeding practices. The study was carried out to collect informations on nutrition education within activities related to supplementary feeding program at government Elementary School (SD) and Islamic Elementary School (Madrasah Ibtidaiyah) in the District of Central Lampung. The findings show that nutrition education activities given by the teachers has not been done properly due to several reasons such as limitation of time availability, and teachers do not have adequate knowledge on food and nutrition leading to the constraint in applying nutrition education. Further training for teachers is needed to enable them to carry out nutrition education within the activities of Supplementary Feeding Program (PM-ASI) in appropriate ways.Keywords: nutrition education, school feeding program (PMT-AS), elementary school children.